ANALISIS RELATIONSHIP MARKETING (PEMASARAN RELASIONAL) DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PT TELKOMSEL BANDAR LAMPUNG - Soewito Soewito; Gheany Febidhanty; Suwandi Suwandi; Agustuti Handayani (SOSIALITA, 2020)
Customer satisfaction is determined by the quality of the goods or services the customer wants, so quality assurance is a top priority for every company as a benchmark for the company's competitive advantage. Quality of service in service companies is very important from the point of view of consumers. The purpose of this study was to determine the effect of relationship marketing and customer satisfaction on customer loyalty of PT Telkomsel in Bandar Lampung. This type of research is quantitative; the population in this study is the customer of PT Telkomsel in Bandar Lampung for 3 months as many as 60 people and a sample of 60people. Analysis of the data used is multiple linear regression analysis. The results of the study found that there is an influence of relational marketing on customer loyalty of PT Telkomsel Bandar Lampung. There is an influence of customer satisfaction on customer loyalty of PT Telkomsel Bandar Lampung. There is the influence of relational marketing and customer satisfaction on customer loyalty of PT Telkomsel Bandar Lampung. Suggestion, PT Telkomsel Bandar Lampung is advised to be able to convince customers with a guarantee of satisfying service supported by professional employees in serving customers. These steps are expected to make customers like the services provided, so that eventually customers will come back and make repeat purchases.